2019
DOI: 10.1002/ange.201901332
|View full text |Cite
|
Sign up to set email alerts
|

Eine peptidvermittelte Selbstspaltungsreaktion initiiert die Tyrosinaseaktivierung

Abstract: Die Umwandlung inaktiver pro-Polyphenoloxidase (pro-PPO) zum aktiven Enzym erfolgt durch die proteolytische Abspaltung seiner C-terminalen Domäne.D ieser Artikel beschreibt einen peptidvermittelten Spaltprozess, der in der Aktivierung von pro-MdPPO1 (von Malus domestica) resultiert. Eine Kombination aus massenspektrometrischen Untersuchungen, Mutationsstudien und Rçntgenkristallstrukturanalysen wurdeanpro-MdPPO1 selbst (1.35 )sowieanzwei separaten C-terminalen Domänen, eine nach Selbstspaltung (C cleaved )v on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Using the monophenolic substrate tyramine, activity was once again observed only after addition of SDS. Therefore, the interactions in-between the two domains appear to be of significant strength and probably resemble the interactions in-between the active and C-terminal domain of MdPPO1 where a self-cleavage reaction in-between those domains did also result in a cleaved but still latent enzyme 16 . Activation of jrPPO1-wt was tested using different molarities of salts (NaCl, KCl, MgCl 2 and CaCl 2 ), all of which resulted in active enzyme with the divalent ions (Mg 2+ and Ca 2+ ) requiring lower molarities than the monovalent ions (Na + and K + ) ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Using the monophenolic substrate tyramine, activity was once again observed only after addition of SDS. Therefore, the interactions in-between the two domains appear to be of significant strength and probably resemble the interactions in-between the active and C-terminal domain of MdPPO1 where a self-cleavage reaction in-between those domains did also result in a cleaved but still latent enzyme 16 . Activation of jrPPO1-wt was tested using different molarities of salts (NaCl, KCl, MgCl 2 and CaCl 2 ), all of which resulted in active enzyme with the divalent ions (Mg 2+ and Ca 2+ ) requiring lower molarities than the monovalent ions (Na + and K + ) ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Removing the C-terminal domain by extensive proteolytic cleavage seems to be a prerequisite to convert the enzyme from its latent state into the active form. Otherwise, the still intact C-terminal domain is presumably held in place by non-covalent forces, blocking access to the active center (pre-active form) 16 .…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning, the pipeline searched for an appropriate template of the investigated sequence (OU702517) based on BLAST 105 and HHblits 106 . The search resulted in Md PPO1 66 , Malus domestica TYR 1 (PDB: 6ELS) 35 , 36 , as the hit which exhibited the highest coverage value (0.86, with 69.80% sequence identity). The final homology model of the pro- Dl PPO1 was then created using the 6ELS structure as the template and visualization was done using the PyMol Molecular graphic system (Schrödinger, LLC) 107 .…”
Section: Methodsmentioning
confidence: 99%
“…sodium dodecyl sulfate, SDS) 17 , 27 33 . Although the natural proteolytic mechanism is unknown 17 , it has recently been reported that plant PPOs are capable of self-activation which can autoproteolytically separate the active enzyme from the C-terminal domain 34 36 .…”
Section: Introductionmentioning
confidence: 99%